Perbandingan Performa Progressive Web Apps dan Mobile Web Terkait Waktu Respon, Penggunaan Memori dan Penggunaan Media Penyimpanan - Muhammad Rasyid Ridho; Aryo Pinandito; Ratih Kartika Dewi (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
Progressive Web Apps (PWA) is a Mobile Web that uses the latest technologies to create a Mobile Web with better user experiences than traditional Mobile Web. Creating a web application with such experiences, one thing that can not be forgotten is performances and the technologies behind it. Speaking of performance, many aspects could be considered, such as responses time, memory usages and storage usages. Thus, this study will discuss about comparisons between PWA and Mobile Web related to those aspects in order to provide some insights and references of this newly introduced technology. From this study, there are some things that can concluded. Response time performance depends on page resources size, caches size and the access frequencies. On a small sized page and small sized cache files, Mobile Web still faster than Progressive Web App, while on large sized page and cache files Progressive Web App is the winner. In memory usages performance, Mobile web uses memory fewer than PWA due to an additional process that PWA has (Service Worker). In storage usages performance, Mobile web is not using any of storage spaces, while the storage usages of PWA depends on the size of the caches stored in the browser.